Effect of the Educational Pamphlet on the Quality of Multiple-Choice Questions - Ferena Sayar; Mahdi Vatanpour; Mahmoud Ghasemi; Mohammad Reza Shabahangfar (Islamic Dental Association of Iran, 2016)
Background and Aim: The aim of this study was to evaluate the structural integrity of multiple-choice questions according to the Millman checklist, and to assess thedistinguishing power of these questions between weak and strong students in theoretical courses of Periodontics in an academic year (2014-15) in Dental Branch of Tehran Islamic Azad University. Materials and Methods: A total of 262 students comprising periodontics module 1, 2 and 3 in two semesters responded to 240 multiple-choice questions and results from the two consecutive semesters were compared with each other. ANOVA was used to analyse data. P<0.05 was considered significant. Results: There was no statistical difference between the difficulty coefficient of the questions in the two semesters for Periodontics module 1, 2, and 3 (P-values were0.2, 0.34 and 0.69, respectively). For discrimination coefficient, there was no significant difference between Periodontics module 2 (P=0.72) and 3(P=0.42) in the two semesters, however, in Periodontics module 1 this difference was significant (P=0.017). Although a favourable change in the indicators of Millman checklist was seen in the second semester, it was not statistically significant (P= 0.65).In total, the difficulty and discrimination coefficients revealed that the majority of questions were "medium difficult". Conclusion: Although the educational pamphlet did not significantly improve the quality of multiple-choice questions, some Millman checklist items improved slightly.                     Key Words: Millman checklist, Discrimination coefficient, Difficulty coefficient, Periodontics, Multiple choice questions (MCQ)